(2x-5)+15=67

Simple and best practice solution for (2x-5)+15=67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-5)+15=67 equation:


Simplifying
(2x + -5) + 15 = 67

Reorder the terms:
(-5 + 2x) + 15 = 67

Remove parenthesis around (-5 + 2x)
-5 + 2x + 15 = 67

Reorder the terms:
-5 + 15 + 2x = 67

Combine like terms: -5 + 15 = 10
10 + 2x = 67

Solving
10 + 2x = 67

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 2x = 67 + -10

Combine like terms: 10 + -10 = 0
0 + 2x = 67 + -10
2x = 67 + -10

Combine like terms: 67 + -10 = 57
2x = 57

Divide each side by '2'.
x = 28.5

Simplifying
x = 28.5

See similar equations:

| 6(y-5)=4(4+y) | | -2x^2+5x+33=21 | | b+21/6=-13/8 | | -2x^2+5x+33=0 | | 6(4-5)=4(4+y) | | -5(2b+7)-7(-b-8)=0 | | 4x+5y=19 | | 2x^2-5x-33=21 | | 3y^2+7=2y | | 6y-30=16+4y | | -48=6(-6h-2) | | 4(2x-5)15=67 | | 7ln(2x+5)=8 | | 4x+5x=19 | | -8+6p=4(7+6p) | | k/100=0.15 | | 9+9n=-162 | | -(7b+7)=-14 | | k/20=0.15 | | k/8=6 | | 8x+12=11X | | g/2=16 | | -22-7n=-6+3(1-2n) | | -6y+9+4y=13 | | 8f=24 | | -3(1x+4)=-4x | | 4a^2+9a+1=0 | | x^2+3x+2=7 | | 5=-7y | | 4y-2=90 | | n^2+8=15n | | -3(8x+2)+3x=7-8x |

Equations solver categories